The Influence of Customer Service on Customer Satisfaction At Bank Jabar Banten Sharia Sub-Branch Office KCP Sumedang - Hamid, Abdul Hamid; Enceng Iip Syaripudin; Gini Gaussian; Sasa Sunarsa (El-Qish: Journal of Islamic Economics, 2024)
One strategy that can support success in the banking business is to try to offer quality services with good and qualified service quality. Customer service is carried out as well as possible to provide comfort to customers so that the customer experience during transactions is better and can meet customer expectations in terms of service. This study aims to determine and analyze the relationship between customer service and customer satisfaction at Bank BJB Syariah KCP Sumedang. This research is a type of quantitative research using questionnaires and observation methods. The data collection techniques used in this study are observation and questionnaires or questionnaires to obtain data on customer service (X) and customer satisfaction at Bank BJB Syariah KCP Sumedang (Y). This study took a population of 113 customers (who had direct contact with customer service during the first quarter of 2023) Bank BJB Syariah KCP Sumedang with a total research sample of 57 respondents. The results of this study indicate that the customer service variable has a positive and significant effect on customer satisfaction at Bank BJB Syariah KCP Sumedang. This is based on the results of the t-test with a sig value <0.05 and based on the results of simple linear regression analysis which has a positive or unidirectional regression coefficient value so that it can be interpreted that better customer service will increase customer satisfaction.